Fish Sanctuaries In The Tonle Sap Great Lake (Cambodia) - Chheng , Phen (2011)
Eight fish sanctuaries namely Pi Stoun, Chroy Sdey, Kampong Preak, Reang Til, Dey Roneat, Park Konteal, Kampong Pluk and Ba Lot are situated in different parts of the Tonle Sap Great Lake. They were established in 1987 with average area of 2,616 ha, to be act as fish refuge during dry season. These sanctuaries are totally protected from fishing activities in the whole year round, as compared to the open access areas where fishing activities are allowed either in the whole year round or in the open fishing season.